Cardioembolic Stroke Due to Prosthetic Valve Endocarditis Caused by Candida parapsilosis: A Case Report - Mohammad Nasser Affas (22225225) (2024)
Embolic stroke due to prosthetic valve endocarditis (PVE) caused by Candida parapsilosis is a rare and serious complication. Successful management requires a combination of medical and surgical approaches. We present a case full of complexities in diagnosing and managing Candida PVE, emphasizing the importance of a multidisciplinary approach. A 50 year‐old male presented to the emergency department with vertigo and low‐grade fever and was found to have cerebellar stroke likely from the cardioembolic origin, and the patient had a history of uncontrolled diabetes and double prosthetic valves. The diagnosis was challenging and required transesophageal echocardiography (TEE) which showed two vegetations attached to the mitral valve prosthesis. The management involved antifungal therapy, but surgery was hindered by financial issues. The patient was considered for the AngioVac vegetation aspiration system due to persistent fungemia. Eventually, surgery was not performed, and the patient was discharged with a plan for long‐term suppressive antifungal therapy. Other Information Published in: Case Reports in Infectious Diseases License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1155/2024/5581547